Advancement in the development of single chain antibodies using phage display technology - Xiaohui Zheng; Qi Liu; Yimin Liang; Wenzhi Feng; Honghao Yu; Chunyu Tong; Bocui Song (PeerJ, 2024)
Phage display technology has become an important research tool in biological research, fundamentally changing the traditional monoclonal antibody preparation process, and has been widely used in the establishment of antigen-antibody libraries, drug design, vaccine research, pathogen detection, gene therapy, antigenic epitope research, and cellular signal transduction research.The phage display is a powerful platform for technology development. Using phage display technology, single chain fragment variable (scFv) can be screened, replacing the disadvantage of the large size of traditional antibodies. Phage display single chain antibody libraries have significant biological implications. Here we describe the types of antibodies, including chimeric antibodies, bispecific antibodies, and scFvs. In addition, we describe the phage display system, phage display single chain antibody libraries, screening of specific antibodies by phage libraries and the application of phage libraries.